ABCs on wings - Olivera, Ramon (Little Simon, an imprint of Simon & Schuster, 2015)
"In this book, kids will learn their ABCs through the amazing world of aviation. From A is for ace to Z is for zeppelin, young children will be introduced to biplanes, carriers, gliders, jets, and many more vehicles of flight. Refreshing and unique, this concept book is filled with bold, graphic illustrations that soar off the pages!"--